(untitled) (Research, Society and Development, 2022)
With the increasing advancement of poultry, problems with management and metabolic changes in birds began to appear on farms, especially heat stress. As it is a country with a tropical climate, temperature diversity is an important stressor to be considered by producers. In addition to thermal stress, several stressors deserve attention from producers, especially in the pre-slaughter management of birds. Capture techniques, improved transport and pre-slaughter waiting time planning are necessary for the best animal welfare, resulting in a better product offered to the consumer. When animals are subjected to adverse conditions, hormonal and hematological stimulation mechanisms are triggered with the intention of preparing and providing the necessary resources for the organism to face the compensatory emergency demands, aiming to maintain its balance. The objective of this literature review is to report the main changes that occur in hematological cells and plasma hormones during stress in poultry production, reporting the future perspectives of these analyses.